Screening of marcescin producing isolates from Serratia marcescens - Ali, Zainab; Khawlah Jebur Khalaf; Hind Hussein Obaid; Raghad Akram Aziz (ASJ - Academic Science Journal, 2024)
The current study intends to investigate the production of bacteriocin from S. marcescens, a Gram-negative bacterium, is a human pathogen and the reason why hospital medical equipment becomes contaminated. Various samples from patients about 220 samples which include blood,urine,abscess and sputum, twenty -three isolates of S.marcescens was performed as per standard laboratory procedure and confirmed by using  VITEK-2 systems.  The isolates of S.marcescens which produced marcescin detected by four methods : spot –on-the –lawn method , Cup-assay method ,Well-diffusion method  and Agar cross streaking  assay , the production of bacteriocin was produced by adding mitomycin-c to the bacterial broth to increase the amount of bacteriocin.